2011
DOI: 10.2478/s11535-011-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of auxins in somatic embryogenesis of Abies alba

Abstract: The somatic embryogenesis of conifers is a process susceptible to exogenous phytohormonal treatments. We report the effects of the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D) and the auxin inhibitor p-chlorophenoxyisobutyric acid (PCIB) on the endogenous level of the auxin indole-3-acetic acid (IAA) and on the anatomical composition of early somatic embryos of Abies alba (European silver fir). The embryogenic suspensor mass (ESM) of Abies alba proliferated on a medium supplemented by 2,4-D as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…For several years, it has been known that the presence of an exogenous auxin can induce the endogenous biosynthesis of IAA. 1,5,6,13 However, it is also possible that the exogenous auxin promotes the inhibition of IAA degradation by reversible conjugating reactions. 52,53 Thus, the homeostasis of the auxins is critical for the induction of the SE process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For several years, it has been known that the presence of an exogenous auxin can induce the endogenous biosynthesis of IAA. 1,5,6,13 However, it is also possible that the exogenous auxin promotes the inhibition of IAA degradation by reversible conjugating reactions. 52,53 Thus, the homeostasis of the auxins is critical for the induction of the SE process.…”
Section: Discussionmentioning
confidence: 99%
“…In D. carota, the level of IAA decreased 10-fold from that of the initial cell clusters, 1 as well as in Abies alba somatic embryos. 13 It has been suggested that in the continuous presence of auxin, carrot cell lines are able to develop into the globular stage, but not beyond. 61 In addition, recently it has been suggested that the removal of exogenous auxin from the medium triggers both auxin polar transport and auxin gradient establishment for SE induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the first week of maturation, this Ax decreases suggesting that the increase in the level of endogenous IAA is important to start the differentiation process. Later, the IAA levels increase again according to the embryo growth, which can be seen as an important mechanism for the correct establishment of cells division patterns and the organization of both shoot and root meristems (Vondráková et al 2011).…”
Section: Auxin Response During the Somatic Embryogenesismentioning
confidence: 99%
“…The overexpression of auxin related proteins in matured somatic embryos of cv. Rasthali revealed that higher concentration of endogenous auxin is required for the maturation of somatic embryos from the globular to the cotyledon stage as also reported in Abies alba (Vondrakova et al ). The embryo development process and pattern are influenced by auxin biosynthesis and polar auxin transport (Moller and Weijers ).…”
Section: Discussionmentioning
confidence: 56%